KETERSEDIAAN TANAH BAGI MASYARAKAT RAWAN BENCANA - Utami, Westi (BHUMI: Jurnal Agraria dan Pertanahan, 2018)
The high threat of disaster / multi-disaster in Indonesia leads to a number of communities in a state of being exposed and vulnerable to disasters. The high number of people living around the source of disaster / KRB III also causes the high degree of potential risk and loss if the disaster occurs. The National Land Agency has pivotal role in regulating land for development, in this case, through the provision and arrangement of land for settlement (relocation) and for infrastructural development for the people living in the disaster-risk areas. This study employed review of literature and legal products on land availability as its method and approach. The allocation of land, particularly for the people living in disaster-risk areas, may be provided through land acquisition, land utilization of reserved State land from previously abandoned land, or may also be provided through land consolidation based on spatial planning.This is intended to achieve the quality of environment, safe and prosperous society. Keywords: land availability, land consolidation, disaster